Modern and Contemporaneous Physics in comics by high school students (Research, Society and Development, 2020)
Modern and Contemporaneous Physics (MCPhys) aren’t different from Classic Physics only by its name or by its meanings. The latter, for being a curricular component of significant importance, and for being a way to understand the world, has its effective approach needs to be addressed at various levels of education as a necessity. The objective of the research was to investigate the way in which High School students realize the educational process MCPhys, when exposed to methodologies with teaching strategies in which they can prove what they have learned. This is a qualitative descriptive-interpretative research that promoted an educational process, in a playful way, through the construction of a comic book that served as a research tool. To understand the data used to read images proposed by Ott (2008). Finally, students showed perceptions of MCPhys on its historical, theoretical state and some scientific statements satisfactorily. This proposal could be used in future by professors as a teaching opportunity to study the FMC in High School because deprive the student of this knowledge in a systematic way, it is also deprive him of one of the intellectual revolutions that this new area of ​​Physics provided to the world.